Light-curve and spectral properties of ultra-stripped core-collapse supernovae leading to binary neutron stars - Moriya, T; Mazzali, P; Tominaga, N; Hachinger, S; Blinnikov, S; Tauris, T; Takahashi, K; Tanaka, M; Langer, N; Podsiadlowski, P (Oxford University Press, 2016)
We investigate light-curve and spectral properties of ultra-stripped core-collapse supernovae. Ultra-stripped supernovae are the explosions of heavily stripped massive stars which lost their envelopes via binary interactions with a compact companion star. They eject only ∼0.1~M⊙ and may be the main way to form double neutron-star systems which eventually merge emitting strong gravitational waves. We follow the evolution of an ultra-stripped supernova progenitor until iron core collapse and perform explosive nucleosynthesis calculations. We then synthesize light curves and spectra of ultra-stripped supernovae using the nucleosynthesis results and present their expected properties. Ultra-stripped supernovae synthesize ∼0.01~M⊙ of radioactive 56Ni, and their typical peak luminosity is around 1042~erg~s−1 or −16 mag. Their typical rise time is 5 − 10 days. Comparing synthesized and observed spectra, we find that SN 2005ek, some of the so-called calcium-rich gap transients, and SN 2010X may be related to ultra-stripped supernovae. If these supernovae are actually ultra-stripped supernovae, their event rate is expected to be about 1 per cent of core-collapse supernovae. Comparing the double neutron-star merger rate obtained by future gravitational-wave observations and the ultra-stripped supernova rate obtained by optical transient surveys identified with our synthesized light-curve and spectral models, we will be able to judge whether ultra-stripped supernovae are actually a major contributor to the binary neutron star population and provide constraints on binary stellar evolution.